(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2026)
This article analyzes the lexical-semantic, stylistic, and aesthetic features of word combinations used in a poet’s poetry. The role of word combinations in creating poetic imagery is examined, and methodological approaches to working with them in the educational process are proposed. The study highlights effective techniques for analyzing poetic texts aimed at developing students’ artistic thinking and linguistic competence. The findings contribute to improving the effectiveness of teaching language and literature through literary texts.